A nonlinear numerical model for sloped bottom tuned liquid dampers. - Olson, D.E.
Shaking table data for a tuned liquid damper with a sloped bottom of 30 degrees with the horizontal are investigated using a non linear numerical model previously developed by Yu, Jin-kyu, Nonlinear characteristics of tuned liquid dampers. Ph D. Thesis, Department of Civil Engineering, University of Washington, Seattle, WA, 98195 (1997). Stiffness and damping characteristics for this model are obtained and compared with those previously derived for box shaped tanks. The value for these parameters reflect the softening spring behaviour of the sloped bottom system in contrast to the hardening system evident for the box shaped TLD. Consequently, the sloped bottom tank should be tuned slightly higher than the fundamental structural frequency in order to obtain the most effective damping.
Keywords: Structural control; Fluid mechanics; Structural dynamics